The Influence of Advertising, Lifestyle, and Packaging On Purchase Decisions of Kopi Kenangan in Batam City - Putri Mayanglay; Wasiman Wasiman (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The purpose of this study is to examine the individual effect of advertising, lifestyle, and packaging on purchasing decisions of Kopi Kenangan consumers in Batam City, as well as to analyze the simultaneous effect of advertising, lifestyle, and packaging on purchasing decisions. This study employs a quantitative descriptive approach using a non-probability sampling technique, namely purposive sampling. The research was conducted in Batam City, where the population size is large and cannot be precisely determined. Based on the Lemeshow formula, a total of 204 respondents were selected as the research sample. Data were collected through the distribution of questionnaires using a Likert scale. Data analysis techniques included validity and reliability tests, multiple linear regression analysis, and hypothesis testing using t-tests and F-tests. The results indicate that advertising, lifestyle, and packaging have a positive and significant effect on purchasing decisions. Effective internet-based advertising enhances brand appeal, lifestyle reflects consumers’ preferences and consumption patterns, and attractive packaging provides added value through product protection and visual appeal, which simultaneously contribute to consumers’ purchasing decisions.